Expanding conservation culturomics and iEcology from terrestrial to aquatic realms - Jarić, Ivan; Roll, Uri; Arlinghaus, Robert; Belmaker, Jonathan; Chen, Yan; China, Victor; Douda, Karel; Essl, Franz; Jähnig, Sonja C; Jeschke, Jonathan M; Kalinkat, Gregor; Kalous, Lukáš; et al. (PLoS biology, 2020)
The ongoing digital revolution in the age of big data is opening new research opportunities. Culturomics and iEcology, two emerging research areas based on the analysis of online data resources, can provide novel scientific insights and inform conservation and management efforts. To date, culturomics and iEcology have been applied primarily in the terrestrial realm. Here, we advocate for expanding such applications to the aquatic realm by providing a brief overview of these new approaches and outlining key areas in which culturomics and iEcology are likely to have the highest impact, including the management of protected areas; fisheries; flagship species identification; detection and distribution of threatened, rare, and alien species; assessment of ecosystem status and anthropogenic impacts; and social impact assessment. When deployed in the right context with awareness of potential biases, culturomics and iEcology are ripe for rapid development as low-cost research approaches based on data available from digital sources, with increasingly diverse applications for aquatic ecosystems.
Keywords: zkreslení výsledků (epidemiologie); zachování přírodních zdrojů; Animals; ekosystém; Fisheries; Ecosystem; rybářství; divoká zvířata; Bias; Endangered Species; zvířata; Conservation of Natural Resources; Animals, Wild; ohrožené druhy